Physical training improved cardiovascular fitness level among chronic obstructive pulmonary disease patients. - Vengatasubramani M,; Vikram M, (Penerbit UKM, 2014)
Chronic obstructive pulmonary disease (COPD) patients are reported to have cardiovascular instability which leads to greater limitation for activities there by leads to poor quality of life. Physical training proved to be one of the moderators of these limitations. However, uncertainty prevails among the protocol and duration. The present study investigated the effect of physical training on blood pressure,heart rate and Rate pressure Product (RPP) among COPD patients. A total of thirty COPD patients aged between 40 to 55 years were recruited for the study based on the inclusion and exclusion criteria and were assigned in to experimental group (15 patients) and control group (15 patients). The mean difference of blood pressure, heart rate and RPP were analyzed using paired t-test. There was significant difference between the pre and post test values of all parameters between experimental and control group with p<0.05. Diastolic blood pressure showed to be less significant compared to the systolic blood pressure. This showed that specifically designed physical improved the cardiovascular fitness among COPD patients.